2019
DOI: 10.1016/j.celrep.2018.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Systems Properties and Spatiotemporal Regulation of Cell Position Variability during Embryogenesis

Abstract: Highlights d Quantification of cell position variability during C. elegans embryogenesis d Positional variability is highly deterministic and temporally dynamic d Positional variability is associated with lineage identity, location, and symmetry d Fate specification and cell-cell junctions contribute to reduction of variability

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Given the early onset of CEH-43 expression, we generated a loss of function allele to test whether it regulates early cell fate specification, and found that ceh-43 mutant allele homozygotes died as embryos ( Figure S4I), identical to that reported in a putative null allele (tm480) of ceh-43 (Doitsidou et al, 2013). As significant defects in fate specification and differentiation usually affect the 3D position of embryonic cells (Schnabel et al, 2006), we systematically quantified cell position phenotypes in ceh-43 mutant embryos using an established method (Li et al, 2019) ( Figure 5F). Indeed, the relative 3D positions of many early embryonic cells differed significantly from wild-type ( Figure 5F and Table S6); furthermore, the vast majority of affected cells were CEH-43-expressing cells or their descendants ( Figure 5G).…”
Section: Ceh-43 Specifically Regulates the Fates And Positions Of Celmentioning
confidence: 52%
“…Given the early onset of CEH-43 expression, we generated a loss of function allele to test whether it regulates early cell fate specification, and found that ceh-43 mutant allele homozygotes died as embryos ( Figure S4I), identical to that reported in a putative null allele (tm480) of ceh-43 (Doitsidou et al, 2013). As significant defects in fate specification and differentiation usually affect the 3D position of embryonic cells (Schnabel et al, 2006), we systematically quantified cell position phenotypes in ceh-43 mutant embryos using an established method (Li et al, 2019) ( Figure 5F). Indeed, the relative 3D positions of many early embryonic cells differed significantly from wild-type ( Figure 5F and Table S6); furthermore, the vast majority of affected cells were CEH-43-expressing cells or their descendants ( Figure 5G).…”
Section: Ceh-43 Specifically Regulates the Fates And Positions Of Celmentioning
confidence: 52%
“…Though reproducibility and variability of morphogenesis have been previously studied [1,23,31] , underlying mechanism still remains unclear due to lack of enough quantitative information from wild-type statistics and mutant phenotypic analysis. So far, with cell positions from 222 wild-type embryos normalized, a precise and reproducible 4D cell-arrangement pattern was reconstructed ( Fig.1G).…”
Section: Establishment Of Wild-type Morphogenesis Reference With Spatmentioning
confidence: 99%
“…In fact, for the majority of mutants, variability in morphological phenotypes between individual cells in an isogenic cell population is likely not driven solely by a genotype‐to‐phenotype relationship, but rather by a combination of smaller contributions from various effects that impact single cells differently depending on their physiological state. A deeper understanding of this variability may also have broad medical implications and should provide insight into the variable penetrance of genes affecting developmental programs and disease genes (Cooper et al , ; Kammenga, ; Li et al , ; Xavier da Silveira Dos Santos & Liberali, ).…”
Section: Discussionmentioning
confidence: 99%